2020
DOI: 10.1136/thoraxjnl-2019-214484
|View full text |Cite
|
Sign up to set email alerts
|

Acute exacerbations of chronic obstructive pulmonary disease: in search of diagnostic biomarkers and treatable traits

Abstract: Acute exacerbations of chronic obstructive pulmonary disease (COPD) are associated with a significant mortality, health and economic burden. Their diagnosis, assessment and management remain suboptimal and unchanged for decades. Recent clinical and translational studies revealed that the significant heterogeneity in mechanisms and outcomes of exacerbations could be resolved by grouping them etiologically. This is anticipated to lead to a better understanding of the biological processes that underlie each type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
127
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 112 publications
(131 citation statements)
references
References 103 publications
(78 reference statements)
1
127
0
3
Order By: Relevance
“…Second, eosinophilic exacerbations are associated with a favorable treatment outcome with steroid treatment but are also associated with an increased risk of exacerbation relapse [32]. The presence of respiratory viruses at exacerbation are predictive for a higher symptom burden and a delayed recovery [33]. Certain risk factors predispose COPD patients to an AECOPD.…”
Section: Acute Exacerbations Of Copdmentioning
confidence: 99%
“…Second, eosinophilic exacerbations are associated with a favorable treatment outcome with steroid treatment but are also associated with an increased risk of exacerbation relapse [32]. The presence of respiratory viruses at exacerbation are predictive for a higher symptom burden and a delayed recovery [33]. Certain risk factors predispose COPD patients to an AECOPD.…”
Section: Acute Exacerbations Of Copdmentioning
confidence: 99%
“…Previous studies reported that the cause of exacerbations is associated with treatment and patient outcomes. [27][28][29][30] This will have to be examined in welldesigned and well-planned prospective registry studies. Fifth, almost all patients (>90% at each center) were treated with antibiotics, and we could not perform any reliable analysis of the impact of concomitant antibiotics use.…”
Section: Discussionmentioning
confidence: 99%
“…(2) the proportion of patients that were using inhaled corticosteroids; (3) the mean FEV 1 of the participants; (4)-(5) same as above; (6) proportion of patients with bacterial co-infection and (7) proportion of patients that received antiviral treatment. For conducting these analyses, we will use a random-effects model and for metaregression analyses of proportions, we will use the inverse variance method with logit transformed proportions.…”
Section: Meta-regression and Sensitivity Analysesmentioning
confidence: 99%